A mixed methods study reviewing consumer experiences for oral health treatment in Medicaid‐eligible children in Florida. (24th May 2021) - Zolnikov, Tara Rava; Garces, Kristin; Masood, Azam; King, Roderick; Robbins, Mary; McGuigan, Katelyn
Abstract: Objectives: Oral health is essential to a person's overall health, well‐being, and dignity; unfortunately, dental caries, which can cause pain and difficulty eating, affect approximately 50 percent of children between 6 and 8 years old. This is in part because Medicaid‐eligible children face numerous obstacles obtaining dental care. To date, there are 74 million Americans who do not have dental coverage or access to dental services, which is strongly associated with race, class, gender, and ethnicity. The objective of this research was to identify barriers to accessing and utilizing children's Medicaid oral health care and services, to evaluate care delivery and quality, and to assist in establishing a more consumer‐driven approach. Methods: A mixed methods study was conducted throughout the state of Florida, using qualitative and quantitative data collection to seek answers to these questions. There were 422 surveys and 39 interviews distributed to Medicaid‐eligible families and individuals across the state; data collection focused on experiences with oral health care, gaps in current access to Medicaid dental care, and concerns when utilizing care. Results: Our study shows the majority of barriers parents face when accessing Medicaid oral health care are due to logistical access issues, such as cost, appointment wait‐times, and confusion surrounding which dental providers accept specific insurance plans. The findings also highlight how location, race, language, and ethnicity impact families who lack preventive dental health services access and how, in turn, families view their own access to dental services. Conclusion: Ultimately, there exists an avenue to implement programs and policies that address existing disparities in oral health to improve health outcomes by increasing access to care and reducing cultural and socioeconomic barriers.